The fabrics of fairytale: stories spun from far and wide - Batt, Tanya Robyn (New York: Barefoot Books, 2000)
Beautiful fabric and mixed media collages illustrate this collection of stories, each of which involves a traditional fiber craft, including weaving, patchwork and batik.
Keywords: Fairy tales; Folklore; Weaving